PENGARUH ETIKA DAN SELF EFFICACY TERHADAPA PRESTASI BELAJAR MAHASISWA (STUDI PADA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TANJUNGPURA PONTIANAK) - -, DAHLAN B B1021141004 (Jurnal Manajemen Update, 2018)
ABSTRACKLearning achievement is a benchmark of students' ability after learning activities for a certain period of time. The learning achievements of the students of the Faculty of Economics and Business at Tanjungpura University are generally varies, there are students who scored high and low as well. Therefore, it is necessary to further study the factors that influence student achievement. Learning achievement is a benchmark of students' ability after learning activities for a certain period of time. The learning achievements of the students of the Faculty of Economics and Business at Tanjungpura University generally differ from those that are high and low. Therefore, it is necessary to further study the factors that influence student achievement. This research aims to test and analyze the influence of ethics and self efficacy towards achievement students of Faculty of Economics and Business at Tanjungpura University. The sample in this study is 100 respondents. The sampling technique used is quota sampling. This study used multiple linear regression data analysis techniques using SPSS version 21.0. The results showed that ethics and self efficacy had a positive and significant effect on the achievement of students at Faculty of Economics and Business, Universitas Tanjungpura with  determination coefficient (adjusted R2) of 49 %, while the remaining 51% was influenced by other variables which are not examined in this study.Keywords: Ethics, Self Efficacy, Student Learning AchievenmentDAFTAR PUSTAKAAgoes & Ardana. (2011).  Etika Bisnis dan                   Profesi. Jakarta: Salemba EmpatArijanto, A. (2012). Etika Bisnis bagi Pelaku Bisnis. Jakarta: PT Rajagrafindo PersadaBandura, A. (1997). Self Efficacy The Exercise of Control. New York: W.H. Freeman & Company.Bandura, A. (1999). Self Efficacy in Changing Societes. New York: Cambridge       University Press.Ghozali, I. (2013). Aplikasi Analisis Multivariate dengan Program IBM SPPS 21. Semarang: Badan Penerbit Universitas DiponegoroGkorezis, Kostagiolas & Niakas. (2017). Linking Exploration to Academic Performance: The Role of Information Seeking and Academic Self Efficacy", Library Management , https://doi.org/10.1108/LM-02-2017-0021Greogory, J. F. (2011). Teori Kepribadian. Jakarta:Salemba Humanika.Goulao, M. F. (2014). The Realtionship betweem Self Efficacy and Academic Achievement in Adult?s Leaners. Athens Journal of Education, Vol. 1, No.3 (Aug), Hal. 237-246.Komari & Djafar. (2013). Work Ethics, Work Satisfaction and Organizational Commitment at the Sharia Bank, Indonesia. International Business Research; Vol. 6, No. 12;Kuncoro (2009). Metode Riset untuk Bisnis dan Ekonomi Edisis III. Jakarta: Erlangga.Najmudin. (2011). Studi Intervensi Etika dan Peningkatan Moral Etika Mahasiswa (Studi Pada Fakultas Ekonomi Universitas Jenderal Soedirman). Jurnal Bisnis dan Ekonomi (JBE), Maret 2011, Hal. 69 ? 83Nurhayati, E. (2016). Psikologi Pendidikan Inovatif. Yogyakarta: Pustaka BelajarPrevin, L. A., Cervone, D. & John, O. P. (2005). Personality: Theory and Research.Hoboken. NJ: WileyRachmawati, T. (2015). Teori Belajar dan Proses Pembelajaran yang Mendidik. Malang: Penerbit Gaya MediaSanusi, A. (2013). Metode Penelitian Bisnis. Jakarta: Salemba Empat.Sardiman. (2011). Interaksi dan Motivasi Belajar Mengajar. Jakarta: Rajawali Press.Sari, L. P. (2012). Pengaruh Muatan Pendidikan Etika dalam Pendidikan Akuntansi Terhadap Persepsi Etika Mahasiswa (Studi Pada Jurusan Akuntansi fakultas Ekonomi dan Bisnis Universitas Brawijaya Malang Angkatan 2009). Jurnal Akuntansi Multiparadigma. Vol 3, Nomor 3, Desember 2012. Universitas Brawijaya.Setiawan, (2006). Meningkatkan Kualitas. Jakarta: Agro Media Pustaka.Sitorus & Wijaya. (2016). Pengaruh Pengaruh Profesionalisme dan Etika Profesi terhadap Kinerja Audit dengan Struktur Auditor sebagai pemoderasi. Media Studi Ekonomi Volume 19 No. 2 ,Juli ? Desember 2016Shkullaku, R.(2013). ?The Relationship between Self Efficacy and Academic Performance in the Context of Gender among Albanian Students.? European Academic Research. Vol.1 No.4 (Jul), Hal.467-478.Slameto. (2010). Belajar dan Faktor-Faktor yang Mempengaruhinya. Jakarta : PT. Rineka Cipta.Sugiyono. (2012). Metode Penelitian Kombinasi(Mixed Methods). Bandung: AlfabetaSugiyono. (2013). Metode Penelitian Pendidikan (Pendekatan Kuantitatif, Kualitatif, dan R&D). Bandung: Alfabeta.Sugiyono.  (2014). Metode Penelitian Bisnis, Bandung :AlfabetaSugiyono. (2015). Statistik untuk Penelitian, Bandung: AlfabetaSukmadinata, N. S. (2005). Landasan Psikologis Proses Pendidikan. Bandung: PT Remaja Rosdakarya.Sulistyo, J. (2010). 6 Hari Jago SPPSS 17. Yogyakarta: Cakrawala.Suryabrata, S. 2010. Psikologi Pendidikan. Jakarta: PT. Raja Garafindo PersadaSurya, M. 2004. Psikologi Pembelajaran dan Pengajaran. Bandung: Pustaka Bani QurasySyah, M. 2014. Psikologi Pendidikan dengan Pendekatan Baru. Bandung: Rosda.Warsito, H. (2009). Hubungan Antara Self Efficacy dengan Penyesuaian Akademik dan Prestasi Akademik (Studi Pada Mahasiswa FIP Universitas Negeri Surabaya). Jurnal Ilmiah Ilmu Pendidikan. Vol.IX, No.1. Hal 29-47.Yuniarti, R. D. (2014). Pengaruh Sikap dan Gender terhadap Prestasi Belajar Bahasa Indonesia pada Siswa SMP Negeri Kelas VII di Kecamatan Sleman Yogyakarta 2013/2014 , Universitas Negeri Yogyakarta, Indonesia.